Multi-functional composite coating based on the dual effects of cooling and exhaust gas degradation - Huang, Peng; Chen, Feng; Cai, Mingming; Gong, Xiangbing; Huang, Xue; Jiang, Yu; Liu, Ziming (Frontiers in Materials, 2024)
High-temperature hazards of asphalt pavement and pollution from car exhaust are two major problems that need to be solved in road construction. In this paper, a multifunctional composite coating has been prepared from the perspective of reducing road temperature and car exhaust degradation. The principle of heat-reflecting coating is used to reduce the road surface temperature. At the same time, the TiO2 aqueous solution with photocatalytic degradation effect is added to the heat-reflective coating material to achieve the purpose of degrading automobile exhaust degradation, creating a new type of multifunctional coating that has both cooling and exhaust degradation effects. In addition, by changing the amount of carbon black, a multi-functional coating with the best coloring is selected, so that it has better functionality and has the most suitable shade for the road surface. Finally, the cooling effect and the exhaust gas reduction effect are examined through indoor and outdoor tests and the slip resistance of the coating is tested using the pendulum method. The results show that the functional coating group has a certain ability of cooling and exhaust gas degradation compared to the normal control group without coating. For the functional coating group with different carbon black content, the functional coating (G2) with 0.9% carbon black content has the strongest overall functionality. The cooling and exhaust gas reduction effects proved to be the best. The surface cooling rate is 5.4°C, while the internal cooling rate is 4.3°C. The cumulative degradation efficiency of CO and NO is found to be 27.77%, and 73.75%, respectively.